Productivity and quality of winter soft wheat varieties and lines sown after different crops and studied by FSBSI ARRIGC named after I.G. Kalinenko - S. N. Gromova; O. V. Skripka; A. P. Samofalov; S. V. Podgorny (Зерновое хозяйство России, 2018)
Productivity and quality of winter soft wheat varieties and lines sown after different crops and studied by FSBSI ARRIGC named after I.G. Kalinenko The study was carried out in 2013-2015 to estimate the effect of various forecrops on the formation of productivity and quality of winter soft wheat varieties and lines in the Rostov region. The objects of the study were 7 varieties and 6 lines of winter soft wheat developed by FSBSI ARRIGC named after I.G. Kalinenko. During the study the average productivity of winter soft wheat sown in bare fallow land ranged from 7.25 to 8.16 t/ha; the productivity of winter soft wheat sown after peas ranged from 6.47 to 7.17 t/ha; the productivity of winter soft wheat sown after sunflower ranged from 6.14 to 7.07 t/ha. According to the productivity the following varieties and lines of winter soft wheat showed the best results, namely ‘Nakhodka’ (8.16t/ha), ‘Kazachka’ (8.10t/ha), ‘1377/06’ (8.08t/ha), ‘1062/09’ (7.91t/ha) and ‘1401/09’ (7.91t/ha) sown in bare fallow; ‘Nakhodka’ (7.17t/ha), ‘Kazachka’ (7.04t/ha), ‘1062/09’ (7.04t/ha) and ‘1491/07’ (7.05t/ha) sown after peas; ‘Kazachka’ (7.01t/ha) and ‘1062/09’ (7.07t/ha) sown after sunflower. According to the amount of protein in winter wheat, the variety ‘Nakhodka’ sown in bare fallow produced 15.01%, the line ‘1401/09’ produced 14.99%; the varieties ‘Nakhodka’ and ‘Aksiniya’ sown after peas produced 14.58% and 14.40% respectively. According to the content of gluten in kernels the varieties ‘Nakhodka’ and ‘Aksiniya’ sown in bare fallow gave 28.1%; sown after peas ‘Nakhodka’ produced 29.4%; the varieties ‘Nakhodka’,‘Aksiniya’ and the line ‘1491/07’ sown after sunflower showed 23.7%, 23.8% and 23.7% respectively. According to SDS-sedimentation the following varieties and lines showed the best results. The varieties ‘Aksiniya’, ‘Kipchak’, the lines ‘1377/06’, ‘1062/09’, ‘1401/09’ sown in bare fallow showed 56-60 ml; the varieties Aksiniya’, ‘Kipchak’, ‘Kazachka’, the lines ‘1377/06’, ‘1062/09’, ‘1401/09’ sown after peas showed 50.3-53 ml’ the variety ‘Kazachka’ and the line ‘1038/07’ sown after sunflower showed 50-50.3 ml.